Diseño de un sistema de costos por órdenes de producción para el área de Fabricación de artículos de carpintería metálica en la Asociación Interprofesionales de Artesanos Mecánicos Operarios y Conexos de la parroquia Ignacio Flores "AIMOC" - Clavijo Guanochanga, Yolanda Estefanía (2020)
This participating project was carried out with the purpose of designing a rate system for production orders. By identifying the budget elements involved in the production process of industrial kitchens in the Interprofessional Association of Operative and Related Mechanical Artisans of the Ignacio Flores Parish “AIMOC”. A focal study was carried out in the “De la Cruz Condor Segundo Ángel” workshop, which maintains similar characteristics with the rest of the association's workshops, which allowed for a generalized vision in the field of study. The questionnaire with open questions addressed to the legal representatives of the association and the owner of the workshop was used as an instrument to collect qualitative information. The deductive methodology formed a fundamental role for the collection of quantitative information by means of observation data sheets where the material involved in the production process, the depreciation of the machinery and times related to man-machine time by the dependence of the Operator use throughout the production process. As a result of the investigation it was determined that the unit production costs of industrial kitchens are: $ 31.17 of movable type; 27.35 of simple structure; 74.70 of the fryers; nevertheless, the unit price of retail sale generates a profit of 37% and retail of 62%, however, the other members of the association generate loss of 15% wholesale and profit of 11% at retail, observing that in certain products they work outside the cost and in others they maintain considerable losses that are not detected by the ignorance of the calculation of the elements of the cost, therefore, it can be evidenced the importance generated by the application of a system of costs for production orders in determining the real costs for decision making.